HPLC analysis and pharmacokinetics of cyclizine - Walker, Roderick Bryan (Rhodes University, Faculty of Pharmacy, Pharmacy, 1995)
The investigations detailed in this dissertation have been conducted to address the paucity of pharmacokinetic information, in published literature, pertaining to cyclizine. The areas of investigation have included the selective quantitation of both cyclizine and its demethylated metabolite, norcyclizine in serum and urine, assessment of stability of both compounds in stored biological samples, dosage form analysis, dissolution rate testing of tablets, and bioavailability and pharmacokinetics following administration of an intravenous solution, and tablets to humans. High-performance liquid chromatography (HPLC) was used as the main analytical technique throughout these studies. An original HPLC method employing ultraviolet detection with a limit of quantitation of 5Î¼g/â„“ was developed for the determination of cyclizine in serum and both cyclizine and norcyclizine in urine, Solid-phase extraction using extraction columns packed with reversed-phase C18 material, and followed by a simple phase-separation step proved successful for the accurate and precise isolation of the compounds. The validated method was applied to the analysis of serum and urine samples from a pilot study in which a single volunteer was administered 50mg of cyclizine hydrochloride. Several samples collected during the pilot study revealed the presence of both drug and metabolite in concentrations below the limit of detection. In order to improve the selectivity and sensitivity of the analytical method an HPLC method with electrochemical detection operating in the "oxidative-screen" mode was developed. The solid-phase extraction procedure was modified slightly and the method found to be precise, accurate, selective and highly sensitive with a limit of quantitation of IÎ¼g/g/l for both cyclizine and norcyclizine in both serum and urine. This method was applied to the determination of both compounds after intravenous and oral administration of cyclizine to humans. HPLC with electrochemical detection was used for the analysis of samples collected during dissolution studies on the batch of tablets used for pharmacokinetic studies. In addition, this method was used to assess content uniformity of the tablets and of samples from the batch of intravenous ampoules of cyclizine lactate. Dissolution studies showed that all tablets tested passed the compendial specifications for cyclizine. Content uniformity assessment revealed that within-batch uniformity existed for both the tablets and ampoules and, therefore, variations in pharmacokinetic parameters for the drug would more than likely be as a result of inter- and intra-individual variability within the subject population. Pharmacokinetic information for cyclizine was obtained following administration of an intravenous bolus dose of cyclizine lactate as a solution, oral administration of cyclizine hydrochloride as a single dose of 50mg and as fixed multiple doses of 50mg every 8 hours for five days. Further information was acquired following administration of single doses of 100mg and 150mg cyclizine hydrochloride. Data collected from these studies were evaluated using both compartmental and non-compartmental techniques. Cyclizine was rapidly absorbed following oral administration with mean kâ‚ = 1.54 hrâ »Â¹ and was found to have an absolute bioavailability (F) of 0.47. The presence of norcyclizine in serum following oral and not intravenous dosing suggests cyclizine is susceptible to "first-pass" metabolism in either the gut wall or the I iver. Mean ClTOT determined following the intravenous dose was 0.865 â„“/hr/kg. The mean ClTOT of 0.823 â„“/hr/kg calculated following oral dosing, using a unique value of F for each subject compared favourahly with that obtained following intravenous dosing. Renal clearance of cyclizine is negligihle indicating that non-renal routes of elimination account for the majority of removal of cyclizine form the body. Cyclizine is extensively distributed and the mean Vz following an intravenous dose was 16.70 â„“/kg. This value is lower than that calculated from all oral studies from which the mean Vz was determined to be 25.74 â„“/kg. Cyclizine is eliminated slowly with a mean elimination tÂ½ = 20.11 hours. Cyclizine dose not appear to follow dosedependent kinetics and therefore, inability to predict steady state levels are more than likely due to accumulation as a result of frequent dosing rather than saturation of elimination mechanisms. Modelling of intravenous data to one-compartment (lBCM), two-compartment (2BCM) and threecompartment models indicated that the pharmacokinetics of cyclizine can be adequately described by a 3BCM. The drug is rapidly distributed into a "shallow" peripheral compartment (Î± = 9.44 hrâ »Â¹ , and kâ‚‚â‚ = 2.09 hrâ »Â¹ ), and slowly distributed to the "deep" peripheral compartment (Î² = 0.451 hrâ »Â¹ and kâ‚ƒâ‚ = 0.120 hrâ »Â¹ ). Modelling of all oral data indicated that a 2BCM best described the pharmacokinetics of the drug, however, distribution to the peripheral compartment is not as rapid as to the "shallow" peripheral compartment following the intravenous dose. Mean distribution parameters were Î± = 0.64 hrâ »Â¹1 and, kâ‚‚â‚ = 0.39 hrâ »Â¹. Mean CITOT following intravenous dosing of 0.70 â„“/hr/kg was similar to the mean CIToT of 0.73 â„“/hr/kg determined after oral dosing. The mean distribution volume at steady state determined following intravenous dosing (17.78 â„“/kg) was lower than that obtained from the oral studies (25.52 â„“/kg). The mean terminal elimination half-lives calculated for cyclizine following fitting of intravenous and oral data was 25.09 hours. In general, mean pharmacokinetic parameters calculated following titting of data to a 2BCM after oral administration correlate closely with those calculated using non-compartmental techniques. However, the pharmacokinetics following intravenous dosing are better described by a 3BCM and a close correlation between parameters estimated using noncompartmental techniques and compartmental techniques is evident when a 3BCM model is used.
Keywords: High performance liquid chromatography; Piperazine; Pharmacokinetics